BALANCED BILINGUAL EDUCATION IN EFL SETTINGS: INSIGHTS FROM A BILINGUAL SCHOOL CASE STUDY - Dewi, Made Raninta Candra; Ni Nyoman Padmadewi (Universitas PGRI Palembang, 2025)
This study aims to describe the implementation of balanced bilingual education in an EFL context. Adopting a basic qualitative research approach, the research focuses on a bilingual elementary school in Singaraja. Data were gathered through classroom observation and interviews, using the researcher, an observation sheet, and an interview guide as instruments. The interview participant was a first-grade classroom teacher. Data analysis was conducted using content analysis. The results indicate that balanced bilingual education is facilitated through the use of bilingual learning media and consistent language use in daily activities. Learning media include both instructional tools used during lessons and materials displayed in the school environment. Language use encompasses communication during instruction, positive reinforcement practices, as well as school policies and routines that support bilingualism.